Theology, Hermeneutics and Philosophical Poetics - Kačerauskas, Tomas (International Studies. Interdisciplinary Political and Cultural Journal, 2012)
The article deals with Heidegger’s attitudes towards theology. Heidegger, stating that existential philosophy and theology are incompatible, advances a thesis of not objectivating poetic thinking. Whereas, Ricoeur’s biblical hermeneutics is based on his theory of metaphor. The lingual act here means the destruction of the old outlook for the sake of the new one. In this dramatic way cognition occurs as a meeting. The poetica thinking of the late Heidegger is also based on a meeting that covers both horizontal coexistence and vertical direction. The author raises the question whether the poetica thinking of the late Heidegger is not theological?